دراسة توصيفية لبعض الطرز الظاهرية للنوع Amygdalus communisفي الساحل السوري (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2018)
تعتبر هذه الدراسة جزءاً من دراستنا القائمة حاليا في مناطق انتشار اللوز في الساحل السوري. تم من خلال هذه الدراسة استخدام القياسات الحيوية على 19 صفة لأجزاء النبات من الورقة حتى البذرة, بغية تحديد طرز مجتمعةً من اللوز موزعة على موقعين في منطقة عين شقاق من محافظة اللاذقية و منطقة يحمور من محافظة طرطوس. ونتيجة للتحاليل الإحصائية لمعرفة الفرق بين الصفات الكمية والنوعية المدروسة تبين وجود 11 طرازاً مظهرياً  Morphotypeمستقلاً استناداً للصفات النوعية والكمية  تنتمي جميعها للنوع A. communis . This study is a part of our present research in  the areas of Almond distribution in the Syrian coast. Biometrics was used on 19 characters of plant portions, starting from leaf till seed, in order to differentiate between two groups of Almond types, which were distributed on 2 areas, Ain Shkak (Lattakia district) and Yahmour (Tartus district). Analysis of variation was used to test the difference between qualitative and quantitative characters. 11 Amygdalus L. morphotypes which belong to the species Amygdalus communis, were found.